The Behavioral and Emotional Profile of Pediatric Tourette Syndrome Based on CBCL in a Chinese Sample - Cui, Yonghua; Chu, Jiahui; Li, Yanlin; Li, Ying (Frontiers in Psychiatry, 2022)
Background Tourette syndrome (TS) is a childhood-onset neuropsychiatric disorder that has a unique status of a quintessentially neuropsychiatric condition at the interface of neurology (movement disorder) and psychiatry (behavioral/emotional condition). However, the behavioral and emotional profile has seemed to be neglected in the literature thus far. This study aimed to investigate the behavioral and emotional profile of TS. Methods A total of 124 patients aged 6–16 years with TS were included in this study, including age- and sex-matched health control, attention-deficit/hyperactivity disorder (ADHD), obsessive-compulsive disorder (OCD), and major depressive disorder (MDD) groups. The Child Behavior Checklist (CBCL) was used to screen the behavioral and emotional profile of the TS and other compared groups. The Yale Global Tic Severity Scale (YGTSS) was used to assess TS tic severity. Analysis of variance (ANOVA) was used to investigate the difference between the TS and other compared groups. Results The results showed that the eight factors of the CBCL had no association with motor tics, vocal tics, or tic severity (p > 0.05). However, positive correlations were identified between functional impairments (subscales of YGTSS) and thought problems (TP) and rule-breaking behavior (RBB). Based on the eight-factor profile of the CBCL, TS showed a similar profile to MDD but different from ADHD and OCD, which showed similar profiles. Conclusions Based on the assessment of the CBCL of TS, it was found that “pure” TS might show fewer behavioral and emotional problems than OCD, ADHD, and MDD. Similar behavioral and emotional profiles were identified between TS and MDD, but not OCD and ADHD. More attention needs to be paid to the thought problems and rule break problems in the CBCL in the screening stage, which might have a potential influence on the functional impairments of TS.